ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI PROVINSI JAWA TENGAH (Students' Journal of Accounting and Banking, 2014)
Fiscal decentralization bring benefits to the area to set its fiscal capacity . Local governments have the opportunity to improve the efficiency of the economy because the government has an advantage in terms of information about the allocation of resources . This study aimed to examine the effect of expenditure of development, Population and Region Gross Domestic Product to Regional Own Revenue (PAD). The samples in this study were 135 districts / cities in Central Java Province . The data used in this study were taken from the fiscal year 2009-2011. This study used secondary data from the realization of the local government budget. The test results concluded that expenditure of development has a positive and significant impact on Regional Own Revenue , Region  Gross Domestic Product has a positive and significant impact on Regional Own Revenue , while the total Population has a negative effect on Regional Own Revenue. This means that the government's decision to allocate expenses / expenditures are more likely to support the economic growth will increase revenue. Keywords: expenditure of development, population, Region Gross Domestic Product (PDRB), Regional Own Revenue (PAD)